If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 6 = 91 Reorder the terms: 6 + 4x = 91 Solving 6 + 4x = 91 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 4x = 91 + -6 Combine like terms: 6 + -6 = 0 0 + 4x = 91 + -6 4x = 91 + -6 Combine like terms: 91 + -6 = 85 4x = 85 Divide each side by '4'. x = 21.25 Simplifying x = 21.25
| (x-8)(5x-4)=0 | | 4y+12=6y+14 | | 12j=16j(j-8) | | (3w-4)(4w+6)= | | 3x-2(-5x+3)=72 | | 7+2(7)=30 | | h=0.5s-5 | | 20-5w=60 | | 6-10m=-54 | | 8-3p=-14 | | X+3y=-15 | | 2v^2-14v=0 | | 2+4n=-10 | | 1x-4x=6 | | 10=-5(3+w) | | 7-2n=5 | | 23x-16871=1000 | | 7(10w+1)= | | (x+2)(x-8)(5x-4)=0 | | 9xy^2+4y-13=0 | | (x-3)=-3x+33 | | 15x+9= | | 24=3-7x | | 2b+2=3p-7 | | 3x-2=2x+13 | | -12x+3=-8x-6 | | (k+4)=7 | | -2(3+4m)=-18 | | 22=-6-2r | | 10-7n=-25 | | y=2.22x+4.40 | | 35=-7(3+t) |